2023
DOI: 10.1088/2051-672x/acaac0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of texture on hydrodynamic journal bearing performance under starvation lubrication

Abstract: The effect of texture on tribological properties of journal bearings operating under starvation lubrication conditions was studied in this paper. The P-θ model with mass conservation boundary conditions was used to accurately predict the oil film distribution in the full oil film/starvation region of the textured bearing; the model was solved numerically, using the finite volume method. Effects of various degrees of starvation lubrication on the tribological performance parameters, such as eccentricity, attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Chen et al (2021aChen et al ( , 2021bChen et al ( , 2021c investigated the impact of surface texture on the dynamic performance of sliding bearings and found that reasonable texture parameters and distribution could reduce friction and increase end discharge, with an optimal texture density and region. Li and Niu (2023) studied the influence of texture on the frictional performance of bearings operating under oil-limited lubrication conditions and concluded that texture could improve load-carrying capacity and operational performance under mild lubrication conditions. Feng et al (2021) researched the fluid dynamic pressure performance of partially grooved bearings under water lubrication conditions and discovered that bearings with both grooves and wall slip exhibited improved lubrication performance compared to bearings without grooves and wall slip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2021aChen et al ( , 2021bChen et al ( , 2021c investigated the impact of surface texture on the dynamic performance of sliding bearings and found that reasonable texture parameters and distribution could reduce friction and increase end discharge, with an optimal texture density and region. Li and Niu (2023) studied the influence of texture on the frictional performance of bearings operating under oil-limited lubrication conditions and concluded that texture could improve load-carrying capacity and operational performance under mild lubrication conditions. Feng et al (2021) researched the fluid dynamic pressure performance of partially grooved bearings under water lubrication conditions and discovered that bearings with both grooves and wall slip exhibited improved lubrication performance compared to bearings without grooves and wall slip.…”
Section: Introductionmentioning
confidence: 99%
“…(2021a, 2021b, 2021c) investigated the impact of surface texture on the dynamic performance of sliding bearings and found that reasonable texture parameters and distribution could reduce friction and increase end discharge, with an optimal texture density and region. Li and Niu (2023) studied the influence of texture on the frictional performance of bearings operating under oil-limited lubrication conditions and concluded that texture could improve load-carrying capacity and operational performance under mild lubrication conditions. Feng et al.…”
Section: Introductionmentioning
confidence: 99%